PELATIHAN PEMBELAJARAN SAINTIFIK BERWAWASAN RAMAH ANAK MENINGKATKAN KOMPETENSI PROFESIONAL GURU - Sudar Sudar (Universitas Ngudi Waluyo, 2021)
The purpose of this study was to improve the competence of teachers in designing child-friendly scientific learning activities through child-friendly scientific learning training activities at SDN 1 Temulus, Mejobo District, Kudus Regency, 2018/2019 academic year. The research was carried out in 2 cycles, each cycle of four stages, namely planning, implementing, observing and reflecting. There has been an increase in teacher competence in designing child-friendly school learning at SDN 1 Temulus. After being given action in the form of child-friendly scientific learning training activities, teacher competence increased in cycle I to 8 teachers (80%) in the good category and 2 teachers (20%) in the sufficient category, and in cycle II to 10 teachers (100%) in good category. So it can be concluded that the workshop for child-friendly school learning models can improve teacher competence in designing child-friendly scientific learning training.